The Use of the Snowball Throwing Model to Increase Student Activeness in Mathematics Learning in Class III of Sd Negeri 064967 Medan Timur - Khairunnisa, Siti; Elfrianto, Elfrianto (Holistic Science, 2025)
This study aims to evaluate the increase in students' active participation in Mathematics lessons through the application of the Snowball Throwing learning model at SD Negeri 064967 Medan Timur. This type of research is Classroom Action Research (CAR) by collecting data using observation sheets and questionnaires during the learning process to measure student activity and their understanding of the learning material. Learning activities are carried out in two cycles, each involving four meetings. In the first stage of the study, the results were 62%. Of these, there were 2 students who were in the sufficient category with a percentage of 10%, while 18 other students were in the good category with a percentage of 90%. In stage II, a significant increase was seen with results reaching 72%. In detail, 15 students obtained the good category with a percentage of 75%, and 5 other students reached the very good category with a percentage of 15%. Based on this data, it can be concluded that grade III students of SD Negeri 064967 Medan Timur showed activeness in learning mathematics.